Value and Virtue in Public Administration
XVII, 327 p.
Keywords: A multidisciplinary analysis of the role of values and virtue in public administration, this book calls for a rediscovery of virtue. It explores ways of enabling the public sector to balance the values that are presently dominant with classic values such as accountability, representation, equality, neutrality, transparency and the public interest.